Method of finite elements in tasks of investigation non-homogeneous unisotropic soil half-space - Цихановський, В.К.; Соколовська, В.А. (Proceedings of National Aviation University (archive), 2004)
The methodology investigation of elastic soil half-space was reduced in the article, what is developing real theory half-space of expense of utilization theory non-linear elastic-plastic of deformation solid body.Fpplicationof the principal correlationsof method finite elements with utilization of momental scheme of finite elements.